The Capacity Gap of Village Apparatus in Public Service Delivery and Its Impact on Public Satisfaction - Pasha Al Hafiz Dafa; Nur Handayani (International Journal of Science and Environment (IJSE), 2026)
Public service is one of the primary functions of village government, which plays a role in meeting the administrative and service needs of the community. However, the quality of public services at the village level still faces various challenges, particularly related to the capacity gap of village officials in carrying out their duties and functions. This study aims to examine the capacity gap of village officials in providing public services and its impact on public satisfaction through a Systematic Literature Review (SLR) approach. The research data were obtained from 10 relevant scientific articles published in the period 2018–2025. The analysis process was carried out descriptively and qualitatively by identifying, grouping, and synthesizing the main findings from various studies related to the capacity of village officials, the quality of public services, and public satisfaction. The results of the study indicate that the capacity of village officials still faces various limitations in the aspects of knowledge, skills, competencies, education levels, utilization of information technology, and professionalism in providing services. This capacity gap impacts the quality of public services, particularly in aspects of speed, accuracy, effectiveness, and responsiveness of services. In addition, good quality public services have been shown to contribute to increasing public satisfaction, while less than optimal services tend to decrease the level of public satisfaction with the village government. Therefore, enhancing the capacity of village officials through education, ongoing training, competency building, and digitalization of services is a crucial strategy for improving the quality of public services and public satisfaction. This research contributes to enriching the study of village official capacity and provides a basis for consideration by the government in formulating human resource development policies at the village level.